Patterns of resource use efficiency in relation to intra-specific competition, size of the trees and resource availability in ponderosa pine - Gyenge, Javier; Fernandez, María Elena (Elsevier, 2019)
Patterns of resource use efficiency (RUE) in relation to intra-specific competition, size of the trees and resource availability are under debate. Also, the relationship between RUE and growth efficiency (GE) seems to be different depending on the genera studied. We test the following hypotheses: (1) RUE of the stand decreases after canopy closure mainly due to the decrease in RUE of the suppressed trees, (2) RUE increases with the availability of resources and/or stand productivity and, (3) the efficiency of use of water, light and nitrogen are positively correlated each other, and are not correlated with GE. We measured or estimated at tree and plot level, the concentration of 13C in wood as a proxy of intrinsic water use efficiency (iWUE), nitrogen productivity (NP), light use efficiency (LUE) and GE in Pinus ponderosa trees growing in two sites in Patagonia, South-America. Within each site, we studied plots with contrasting intra-specific competition due to different plantation density. A decrease in NP and GE at plot level followed canopy closure, with no decrease in LUE or iWUE. In contrast to Hypothesis 1, the decrease in RUE of a stand, when it was observed, was due to a decrease in the efficiency of resource use of the dominant trees. The suppressed trees seem to always have low RUE, independently of canopy closure of the stand. The trend of a positive relation of RUE and resource availability is rather weak as a generalization (in contrast to Hypothesis 2), but it depends on the resource which use efficiency is analyzed. At plot level, NP, iWUE and GE did not present a correlation with stand productivity. Considering iWUE, no positive correlation was observed with tree size, which contrasts with previous findings. On the other hand, clear and positive relationships were observed between GE and NP with tree growth, supporting the hypothesis of higher RUE in those trees which are growing faster within the stand, which in turn are those which are surely accessing to more resources (soil resources and radiation). The third hypothesis stated in this study was not supported by our results. The only significant correlation was that observed between NP and GE, with no correlation at all between iWUE and the other resources use or growth efficiency.